The Effect of Calcium and Magnesium on Rabbit Blood Platelet Aggregation in Vitro - Hovig, Torstein (Thrombosis and Haemostasis, 1964)
The effect of calcium and magnesium on the aggregation of rabbit blood platelets in vitro was studied, with the following results:1. Platelet aggregation induced by ADP or collagen could be prevented by EGTA or EDTA. The aggregating effect was restored by recalcification. The effect was also restored by addition of magnesium in EDTA-PRP, but not in EGTA-PRP unless a surplus of calcium was present.2. Calcium remained in concentrations of the order of 0.15–0.25 mM after dialysis or cation exchange of plasma. Aggregation of washed platelets resuspended in such plasma could not be produced with ADP or collagen, unless the calcium concentration was increased or that magnesium was added.3. The adhesiveness of blood platelets to collagen was reduced in EGTA-PRP and EDTA-PRP. Release of ADP from platelets influenced by collagen could not be demonstrated either in EGTA-PRP (presence of magnesium) or in EDTA-PRP.4. It is concluded that calcium is a necessary factor both for the reaction leading to release of ADP and for the the aggregation produced by ADP.5. Thrombin induced aggregation of washed platelets suspended in tris-buffered saline in the presence of calcium. No effect of magnesium could be observed unless small quantities of calcium were present.